Numerical Assessment of a One-Mass Spring-Based Electromagnetic Energy Harvester on a Vibrating Object - CHIU, Min-Chie; CHANG, Ying-Chun; YEH, Long-Jyi; CHUNG, Chiu-Hung (Archives of Acoustics, 2016)
The paper is an exploration of the optimal design parameters of a space-constrained electromagnetic vibration-based generator. An electromagnetic energy harvester is composed of a coiled polyoxymethylen circular shell, a cylindrical NdFeB magnet, and a pair of helical springs. The magnet is vertically confined between the helical springs that serve as a vibrator. The electrical power connected to the coil is actuated when the energy harvester is vibrated by an external force causing the vibrator to periodically move through the coil. The primary factors of the electrical power generated from the energy harvester include a magnet, a spring, a coil, an excited frequency, an excited amplitude, and a design space. In order to obtain maximal electrical power during the excitation period, it is necessary to set the system’s natural frequency equal to the external forcing frequency. There are ten design factors of the energy harvester including the magnet diameter $(D_m)$, the magnet height $(H_m)$, the system damping ratio $(ζ_{\rm sys})$, the spring diameter $(D_s)$, the diameter of the spring wire $(d_s)$, the spring length $(\ell_s)$, the pitch of the spring $(p_s)$, the spring’s number of revolutions $(N_s)$, the coil diameter $(D_c)$, the diameter of the coil wire $(d_c)$, and the coil’s number of revolutions $(N_c)$. Because of the mutual effects of the above factors, searching for the appropriate design parameters within a constrained space is complicated. Concerning their geometric allocation, the above ten design parameters are reduced to four ($D_m$, $H_m$, $ζ_{\rm sys}$, and $N_c$). In order to search for optimal electrical power, the objective function of the electrical power is maximized by adjusting the four design parameters ($D_m$, $H_m$, $ζ_{\rm sys}$, and $N_c$) via the simulated annealing method.Consequently, the optimal design parameters of $D_m$, $H_m$, $ζ_{\rm sys}$, and $N_c$ that produce maximum electrical power for an electromagnetic energy harvester are found.